Intergenerational effects: child and maternal outcomes related to exposure to intimate partner violence and trauma in a South African community - Barnett, Whitney Christine (Department of Psychiatry and Mental Health, 2021)
Intimate partner violence (IPV) constitutes a major global health problem, affecting one in three women worldwide at some point during their life. IPV is particularly high in low and middle income countries (LMICs) and is associated with a wide range of adverse maternal and child health outcomes. Despite evidence that exposure to IPV affects child development and growth at birth and in infancy, there are limitations to our existing knowledge. First, few studies have considered the impact of maternal emotional IPV separately on child outcomes investigated, focusing primarily on physical and/or sexual IPV. Second, much of the existing data derives from high income countries, rather than from LMIC settings, where the majority of the world's child population lives and where many children are exposed to disproportionately high levels of poverty and violence-related risk factors. Third, there is limited information from well characterized longitudinal studies in these settings and a lack of investigation of associations in very young children, despite the fact that children under 2 years may be particularly at risk for long-term health sequelae relating to IPV exposure. Lastly, few studies have formally investigated potential mediators, inclusive of both behavioral and biological mechanisms underlying associations between IPV and food security and early-life child growth or development. In high-risk settings such as South Africa it is critical to gain improved understanding of pathways by which violence affects child health. This may be especially important given that LMIC contexts often have fewer programs in place to address IPV, and that associated mental health issues and risk factors may be different than in higher income countries. This thesis aimed to investigate IPV in a South African birth cohort, the Drakenstein Child Health Cohort, to understand better the patterns of IPV amongst pregnant and postpartum women, the impact antenatal and postnatal IPV exposure may have on their child's growth and development, and the pathways by which IPV may impact child health sequelae. Chapter 1 reviews the relevant literature, discusses key gaps and presents thesis aims and structure. Chapter 2 comprises a methods chapter which provides an overview of the study population, measures and ethical considerations. Chapter 3 (Paper 1) presents longitudinal profiles of maternal IPV exposure by sub-type from pregnancy through 24 months post-partum and associations between maternal childhood maltreatment and longitudinal frequency and severity of IPV. Chapter 4 (Paper 2) investigates the association between maternal childhood trauma as well as IPV and food insecurity among pregnant women, and examines whether maternal depression mediates these relationships. Chapter 5 (Paper 3) investigates associations between IPV sub-types and growth at birth and 12 months. Further, multiple psychosocial (substance use, depression) and clinical factors (number of hospitalizations) are tested to determine whether any of these may be mediators in the relationship between IPV and child growth. Chapter 6 (Paper 4) investigates emotional, physical and sexual IPV and their relationship with child development at 24 months of age, and whether depression or maternal alcohol dependence mediates these relationships. Chapter 7 presents a summary of findings across results chapters and includes recommendations for future policy and research. Key findings in this population show that: i) a high proportion of mothers are exposed to chronic IPV during and after pregnancy and that maternal childhood abuse or neglect is associated with higher frequency and severity of IPV exposure; ii) maternal IPV and childhood trauma are each associated with food insecurity during pregnancy and that depression partially explains these relationships; iii) emotional and physical IPV are associated with reduced fetal growth and reduced growth through infancy, and maternal substance use (alcohol or tobacco) partially explains these relationships; iv) both emotional and physical IPV are associated with poorer child development at 2 years, and neither maternal current depression nor alcohol dependence explain these relationships. Overall, the findings highlight that emotional IPV in addition to physical IPV is a key risk factor for child growth and development, and identify potential pathways underlying explored relationships. Maternal depression and substance use emerged as partial explanatory variables for nutritional outcomes, specifically food insecurity during pregnancy and growth outcomes at birth and through infancy. The high prevalence of IPV and its negative impact on child health, together comprise a major public health problem, causing significant hardship and representing a significant burden for families, economies and health systems. Findings presented in this thesis suggest that comprehensive and intersectoral programs are needed to 5 address IPV and associated adverse child health outcomes, inclusive of efforts to address maternal mental health and substance use. Further, it is also vital to ensure emotional IPV is included in training and intervention efforts. Clinical implications and areas for future research are discussed.